A Troublesome Cough: From Diagnosis to Treatment 2017
DOI: 10.1136/thoraxjnl-2017-210983.38
|View full text |Cite
|
Sign up to set email alerts
|

S32 Cough suppression test: a novel objective test for chronic cough

Abstract: IntroductionA recent functional MRI study has shown that patients with chronic refractory cough (CRC) have reduced activity in the areas of the brain associated with cough suppression. Cough challenge tests focus only on provoking cough and have limited clinical application due to the wide overlap between healthy subjects and patients with cough. We investigated whether patients with CRC could suppress cough in a cough challenge test.MethodsWe recruited 13 chronic refractory cough patients and 11 healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Vertigan et al (2006) found a significantly greater improvement in patient rated cough severity score in the intervention group than the control group. Hutchings et al (1993) and Cho et al (2017) whereby the participants received increasing dosages of capsaicin and were instructed to try to not cough. This would give an idea of the patients' ability to suppress their cough which may be a more appropriate outcome measure as it would give greater insight into the effectiveness of their cough suppression ability post intervention.…”
Section: Treatment Effects Of Non-pharmacological Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vertigan et al (2006) found a significantly greater improvement in patient rated cough severity score in the intervention group than the control group. Hutchings et al (1993) and Cho et al (2017) whereby the participants received increasing dosages of capsaicin and were instructed to try to not cough. This would give an idea of the patients' ability to suppress their cough which may be a more appropriate outcome measure as it would give greater insight into the effectiveness of their cough suppression ability post intervention.…”
Section: Treatment Effects Of Non-pharmacological Interventionsmentioning
confidence: 99%
“…Instead previously used measures of cough suppression may be more appropriate such as Hutchings et al (1993) and Cho et al (2017) whereby the participant receives increasing dosages of capsaicin and are instructed to try to not cough.…”
Section: Outcome Measures Usedmentioning
confidence: 99%